Reduction and hierarchization of the SPRINT-E scale for the primary diagnosis of post-traumatic stress syndrome in university students - Bricio-Barrios, E.E.; Arceo-Díaz, S.; Bricio-Barrios, J.A.; García-Rodríguez, R. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2025)
Post-traumatic stress syndrome is a disorder caused by a person's direct or indirect exposure to a situation that has violated their physical and emotional health. If the affected person does not receive treatment, they are prone to alcohol and drug use and, in severe cases, suicide. Before receiving specialized care, primary or screening tests allow identifying people at risk of acquiring this syndrome and referring them to mental health specialists. Instruments that allow for a comprehensive diagnosis usually contain a large number of questions in their assessment scales. However, this forces the people being assessed to answer numerous questions, which can cause them emotional distress due to the effort involved in answering all the questions to be assessed. In this context, a system based on the minimization of questions using the theory of rough sets forming a reduct that makes up the original instrument is proposed. With the reduct obtained, decision trees are used to create a sequence of questions that allows for an assessment to be obtained in less time than that required to answer the full version, without sacrificing diagnostic power. Since the rough set theory does not depend on the amount of data, this study focused on assessing the mental health of students from different semesters who were pursuing a Bachelor's Degree in Medicine, and enrolled at the University of Colima, Mexico. Using a Google Forms template, the 11-question SPRINT-E scale was applied at two moments after the 7.7-magnitude earthquake on the Richter scale that affected the city of Colima, Mexico, on September 19, 2022. The survey had the participation of 158 students in the September survey and 42 in November. The results showed that women obtained an internal reliability greater than 0.9. The survey answered by men in September had a Cronbach's alpha of 0.948 and was not evaluable in November. The diagnosis for men was negative in both periods. On the other hand, in women, ten positive and two negative primary diagnoses were recorded in September, while in November, two cases decreased and no false positives were reported. Rough set theory allowed reducing the number of questions on the SPRINT-E scale from 11 to 4, and decision trees were used to establish the hierarchical order and cut-off points to identify a positive, negative, and false positive primary diagnosis. Finally, the tree model was validated with the November data, showing the same diagnoses regarding the full scale. This study does not intend to replace the primary diagnoses of post-traumatic syndrome, but offers the interviewer a reduced version of questions that, in case that the participant responds with the highest intensity, proceeds with the rest of the validation scale in order to channel the affected persons more efficiently to a mental health specialist.
Keywords: Decision tree; Earthquake; Rough sets; Post-traumatic stress syndrome